Description of the flow in a linear cascade with an upstream cavity part 2: Assessing the loss generated using an exergy formulation (draft). (15th March 2020) - Fiore, M.; Gourdain, N.; Boussuge, J.-F.; lippinois, E.
Highlights: The exergy formulation can be used in LES for gas turbine performance assessment. The losses are attributed to boundary layers and passage secondary vortices. An increase of the purge flow rate promotes more energetic secondary vortices. The overlapping seals promote a delayed development of secondary vortices. Abstract: Purge air is injected in cavities at hub of axial turbines to prevent hot mainstream gas ingestion into interstage gaps. This process induces additional losses for the turbine due to an interaction between purge and mainstream flow. To deal with this issue, this paper is devoted to the study of a low speed linear cascade with an upstream cavity at a Reynolds number representative of a low-pressure turbine using RANS and LES with inlet turbulence injection. Different rim seal geometries and purge flow rates are studied. Details about numerical methods and comparison with experiments can be found in a companion paper. The analysis here focuses on the loss generation based on the description of the flow and influence of the turbulence introduced in the companion paper. The measure of loss is based on an exergy analysis (i.e. energy in the purpose to generate work) that extends a more common measure of loss in gas turbines, entropy. The loss analysis is led for a baseline case by splitting the simulation domain in the contributions related to the boundary layers over the wetted surfaces and the remaining domain (i.e. the complementary of boundary layers domains) where secondary flows and related loss are likely to occur. The analysis shows the strong contribution of the blade suction side boundary layer, secondary vortices in the passage and wake at the trailing edge on the loss generation. The study of different purge flow rates shows increased secondary vortices energy and subsequent loss for higher purge flow rates. The rim seal geometry with axial overlapping promotes a delayed development of secondary vortices in the passage compared to simple axial gap promoting lower levels of loss.